The Drosophila 110-kDa transcription factor TFIID subunit directly interacts with the N-terminal region of the 230-kDa subunit. - Kokubo, T (1993)
Transcription initiation factor TFIID is a multimeric protein complex that plays a central role in transcriptional regulation by facilitating promoter responses to various activators. cDNAs encoding the 110-kDa subunit of Drosophila TFIID (p110) were isolated with a degenerate oligodeoxynucleotide probe based on an amino acid sequence of the purified protein. The entire cDNA sequence contains an open reading frame encoding a 921-amino acid polypeptide with a calculated molecular mass of 99,337 Da. The recombinant protein expressed in Sf9 cells via a baculovirus vector interacts directly with the 230-kDa subunit of TFIID (p230). Together with the previous observation that the TATA box-binding subunit of TFIID (TFIID tau or TBP) interacts directly with only p230 among the TFIID subunits, this result suggests that p110 forms a complex with TFIID tau via p230. A binding study using various p230 mutants indicated that both p110 and TFIID tau interact with the N-terminal 352-amino acid portion of p230, suggesting a functional communication between p110 and TFIID tau via p230 interactions.